2020
DOI: 10.17582/journal.pjar/2020/33.3.508.515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Rate on Yield Components and Grain Yield of Ridge Sown Wheat Varieties

Abstract: W heat (Triticum aestivum L.) is the major staple food cereal crop in most of the countries and cultivated in wide range of environments. Its yield is greatly influenced by crop management factors. Among several crop management factors sowing method, seeding rate and selection of appropriate genotype have prime role in affecting wheat productivity (Chauhdary et al., 2016;Isidro-Sánchez et al., 2017). Appropriate sowing method not only aids in establishment of proper crop stand but also improves the conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…W ider row spacing (18 cm) produced the significantly higher number of tillers (68) and spikes (12.10) per metre row length over narrow row spacing (12 cm) and the higher grain yield (49.13) recorded at 18 cm row spacing which was statistically at par as 15 cm row spacing. These results are supported with Iqbal et al (2020). The grain yield and harvest index was registered with spacing 15 cm as 48.93q/ha and 40.53 per cent, respectively.…”
Section: Grain Yieldsupporting
confidence: 85%
“…W ider row spacing (18 cm) produced the significantly higher number of tillers (68) and spikes (12.10) per metre row length over narrow row spacing (12 cm) and the higher grain yield (49.13) recorded at 18 cm row spacing which was statistically at par as 15 cm row spacing. These results are supported with Iqbal et al (2020). The grain yield and harvest index was registered with spacing 15 cm as 48.93q/ha and 40.53 per cent, respectively.…”
Section: Grain Yieldsupporting
confidence: 85%
“…Increases the seeding rate resulted in a linear increase in grain yield, with a significant rise of 23.5% ( Table 4 ). This increase in grain yield was attributed to a higher number of productive tillers per meter square [ 29 ]. These findings suggest that adjusting the seeding rate based on the specific cultivation conditions could play a crucial role in addressing food insecurity, particularly in developing nations.…”
Section: Discussionmentioning
confidence: 99%
“…Te current result is in agreement with Adinew [28] and Amare [8] who found that maximum productive tiller was recorded from minimum seed rate and vice versa under rain-fed conditions. On the other hand, Iqbal et al [65] reported that maximum productive tillers were obtained at 200 kg ha −1 seed rates than at lower seeding rates under rain-fed conditions.…”
Section: Crop Growth and Yield Components Of Bread Wheatmentioning
confidence: 97%